Determinant of Return On Invested Capital: Empirical Study of Registered Conventional Commercial Banks on the Indonesian Stock Exchange for the 2017 - 2021 period - Munawar, Aang; Harianty, Feby (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The banking sector is one of the most important sectors for the modern economy, because almost every industry involved in financial activities always requires banking services. This encourages the banking industry to function properly as seen from the capital it has. The amount of Third Party Funds for commercial banks continues to increase, reflecting that banking growth is getting better. Therefore, it is important to assess banking financial performance as measured by banking financial ratios. This is the reason why researchers are interested in conducting research on what influences the ROIC of Conventional Commercial Bank Companies. This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), Net Interest Margin (NIM), Cash Ratio (CR), and Intellectual Capital (IC) on ROIC in Conventional Commercial Bank companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The type of research used in this research is quantitative research with non-probability sampling technique using purposive sampling design. The population in this study were 46 banking sub-sector companies listed on the Indonesia Stock Exchange. The type of data used in this study is secondary data in the form of annual financial reports of conventional commercial bank companies listed on the Indonesia Stock Exchange for 2017-2021. The data analysis technique used is the eviews 10 program. The processing method used in this study is panel data regression analysis. The results showed that partially there was a significant influence on Net Interest Margin (NIM) (regression coefficient value of 2.112874, t count value 2.973486 > t table 2.034515 and a significant value of 0.0070 <0.05) and Cash Ratio (CR) ( regression coefficient value of 0.001887, t count value 4.640386 > t table 2.034515 and a significance value of 0.0001 <0.05) on ROIC. While Capital Adequacy Ratio (CAR) (t-count value 0.598328 <t-table 2.034515 and significance value 0.5557> 0.05), Loan to Deposit Ratio (LDR) (t-count value 1.310563 <t table 2.034515 and significance value 0.2035 > 0.05) , Non Performing Loans (NPL) (t count value 0.393639 < t table 2.034515 and a significance value of 0.6976 > 0.05), and Intellectual Capital (IC) (t count value 0.948279 < t table 2 .034515 and a significance value of 0.3533 > 0.05) partially had no effect on ROIC. In addition, the results of simultaneous research Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), Net Interest Margin (NIM), Cash Ratio (CR), and Intellectual Capital (IC) affect ROIC is indicated by the calculated f value of 65.88711 > f table of 2.445259 and a significance value of 0.000000 <0.05. Keywords: CAR, LDR, NPL, NIM, IC, ROIC